2021
DOI: 10.3390/antibiotics10080888
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibiotics in Surface-Groundwater. A Tool towards the Ecopharmacovigilance Approach: A Portuguese Case-Study

Abstract: Environmental monitoring, particularly of water, is crucial to screen and preselect potential hazardous substances for policy guidance and risk minimisation strategies. In Portugal, extensive data are missing. This work aimed to perform a qualitative survey of antibiotics in surface- groundwater, reflecting demographic, spatial, consumption and drug profiles during an observational period of three years. A passive sampling technique (POCIS) and high-resolution chromatographic system were used to monitor and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…The presence of trimethoprim in WWTPs was especially widespread in this study, appearing in the entirety of the effluents and showing an average concentration near 400 ng/L. However, concentrations of this substance up to 1866 ng/L have been reported in several WWTPs in Greece [59].…”
Section: Antibiotics Presence In Wastewatersmentioning
confidence: 51%
“…The presence of trimethoprim in WWTPs was especially widespread in this study, appearing in the entirety of the effluents and showing an average concentration near 400 ng/L. However, concentrations of this substance up to 1866 ng/L have been reported in several WWTPs in Greece [59].…”
Section: Antibiotics Presence In Wastewatersmentioning
confidence: 51%
“…Both pork and groundwater can have high concentrations of enrofloxacin residues, so the human intestinal bacterial community is also at risk of exposure to enrofloxacin ( 24 , 52 , 53 ). This study revealed that exposure to enrofloxacin can cause changes in the structure and function of the intestinal bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…They have been transferred by leaching into environmental water systems such as surface and underground water systems, which can serve as drinking water sources. 3 Authors have detected antibiotics in different drinking water sources, [4][5][6] and due to the current challenge of incomplete removal of antibiotics in treated drinking water sources, antibiotic contaminated water sources have become worrisome. A recent study has reported the presence of antibiotics in bottled water and other drinking water sold on the market.…”
Section: Introductionmentioning
confidence: 99%